CORRELATES OF DOMESTIC VIOLENCE, AGE AND SEXUAL SATISFACTION IN ANTEPARTUM DEPRESSION: A STUDY OF PREGNANT WOMEN IN ANAMBRA STATE - Okoye , Chinwe F.; Ezeonuegbu, Chinyereugo C.; Nwilo , Chinenye M.; Amaefuna , Ogechukwu B. (Int'l Journal of Education Research and Scientific Development, 2025)
This study investigated the extent to which domestic violence, age, and sexual satisfaction correlate with antepartum depression among pregnant women in Awka, Anambra State. A purposive sample of 156 women, aged 19 to 44 years (M = 31.4, SD = 7.58), participated in the study. The research adopted a correlational design and utilized three standardized instruments: Domestic Violence Scale, Sexual Satisfaction Scale, and the Depression Scale specifically adapted to measure antepartum depressive symptoms. Pearson Product Moment Correlation was employed to analyze the data. Findings revealed a significant positive correlation between psycho-physical violence—a subdimension of domestic violence—and antepartum depression (r = 0.499, p < 0.05), suggesting that physical and psychological abuse markedly elevate the risk of depressive symptoms during pregnancy. Conversely, the control-based dimension of domestic violence showed a negative but non-significant correlation with antepartum depression (r = -0.093, p > 0.05), indicating a limited or inconsistent association. Overall domestic violence was significantly and positively associated with antepartum depression (r = 0.426, p < 0.05), emphasizing the cumulative psychological toll of abusive environments. Age was not found to be a significant predictor of antepartum depression (r = -0.032, p > 0.05), suggesting that vulnerability to depressive symptoms in pregnancy may be more influenced by psychosocial than demographic variables. Notably, sexual satisfaction demonstrated a significant inverse relationship with antepartum depression (r = -0.376, p < 0.05), implying that higher levels of sexual fulfillment serve as a protective factor against maternal depressive symptomatology. These findings highlight the urgent need for integrative maternal mental health interventions that account for intimate partner dynamics and sexual well-being. It is therefore recommended that public health initiatives should focus on screening for domestic abuse and addressing relational distress during antenatal care. Keywords: